The black book of colors - Cottin, Menena; e; Amado, Elisa (Toronto ; Berkeley : Groundwood Books, 2008)
This title invites readers to imagine living without sight through remarkable illustrations done with raised lines and descriptions of colors based on imagery. Braille letters accompany the illustrations and a full Braille alphabet offers sighted readers help reading along with their fingers.
Translation of: El libro negro de los colores.
Text in English.
Keywords: Colors -- Juvenile literature; Touch -- Juvenile literature; Blind -- Books and reading; Braille books; Couleurs -- Ouvrages pour la jeunesse; Toucher -- Ouvrages pour la jeunesse; Color; Touch